Environmental Aspects of the Use-Phase for Bearings in Trains - Jonasson, Karl (My University, 2003)
This master thesis was performed in co-operation with SKF Sverige AB and the Department of Environmental Systems Analysis at Chalmers. The purpose of the project is to investigate the environmental aspects of the usephase for bearings in trains. A Life Cycle Assessment (LCA) has been made, and together with earlier results, it is intended to give a deeper understanding of the environmental performance for the whole life cycle of bearings. The environmental impact related to the use of wheel bearings in three generations of trains is studied, and comparisons are made between processes within the life cycle of the bearings, and between the bearings in the different generations of trains. The environmental aspects are related to friction losses when the bearings are in operation, and the use of electricity, water, detergents and oil products during maintenance. The results show that the largest emissions of the use-phase for the bearings are related to electricity use caused by friction losses when the bearings are in operation in the trains. The emissions relation between operation and maintenance varies with the way the electricity is produced, but the emissions from operation are up to 1 000 times higher. The electricity use related to the bearings is up to 30 percent higher for the heavy train with Spherical Roller Bearings (SRBs), compared to the lighter one with the same bearings and the heavier one with Taper Bearing Units (TBUs). When the mass of the trains is considered, the bearings in the train with TBUs show a 30-40 percent lower electricity use. The environmental impact related to the transport of the trains to a wheel axle dismounting site can be of the same size as that from trains bearings in operation, if a detour of about 500 km or more is needed. During maintenance, most electricity is used for heating of washing water and heating of SRBs for mounting. The emissions from naphtha production, oil and grease production and waste oil handling are noticeably lower for the maintenance of TBUs, due to lower grease use, and the use of water and detergent for washing, instead of naphtha. The study can be used as a motivation to perform more explicit investigations of the environmental impact of different construction, maintenance and transports alternatives, and of how to include the results in product development and everyday work.
Keywords: Miljöteknik; Environmental engineering